The ASURA I harvestman-like hexapod walking robot: compact body and long leg design. (1st December 2016) - Hodoshima, Ryuichi; Ohura, Yoshikazu; Nishiyama, Yuki; Sakaki, Akihiro; Watanabe, Soichiro; Kotosaka, Shinya
Graphical Abstract: Abstract : This paper reports the design of a new hexapod walking robot, ASURA I, inspired by the physical features of a harvestman's behavior. ASURA I has a special mobile form with one compact body and much longer legs than conventional hexapod walking robots. This form enhances the walking performance of the robot on rocky or uneven terrain. Here, we present the design and analysis of the leg mechanism, body structure design, gait planning, and prototype development. The long legs (relative to the body) are managed by special parallel link mechanisms, which powerfully and effectively drive the leg joints. The leg mechanism is analyzed by its kinematics, singularity, and static characteristics. The leg length and weight of ASURA I is 1.3 m and 27 kg, respectively. The alternating tripod and wave gaits of ASURA I are successfully demonstrated in a series of walking experiments. Abstract :